Documents on Cyprus - –, – (Études helléniques / Hellenic Studies, 1996)
The European Parliament UNITED NATIONS FORCE IN CYPRUS - UNFICYP Press Release - The Demonstrations of 11 August 1996 Press Release - The Demonstrations of 14 August 1996